The Missing Third Question - Kocani, AleksandÃ«r (Richtmann Publishing, 2013)
This is about a question that could have been put logically by Einstein or anyone that has followed his way of reasoning,following two other guided or heuristic questions. In the literature that analyses Einsteinâ€™s scientific work, it is said that in hisanalysis of so-called mechanical principle of relativity, he was trying to understand if there was something in the laws of naturethat was justifying it. Logically, a question comes up: Did something exist in laws of nature that conditioned discrimination inidentification possibilities of the difference between mechanical experiments from one side and optical, magnetic etc. ones onthe other? Why in principle was impossible for mechanical experiments to identify this difference, but it was not for, say, opticalexperiments? Einstein by his principle of restricted relativity gives an answer to this question. He did the same for â€œWhyâ€-s ofprincipal impossibility to differentiate the rest from the straight-lined uniformed motion by any physical experiment carried withina system of reference. Now is the time to ask the third â€œWhyâ€ which logically follows the two mentioned and to propose ananswer. That is the â€œWhyâ€-s of principal impossibility to differentiate the immobility (or the rest) from the any mechanical motionby any physical experiment carried within a system of reference.